Additional file 6 of Revisiting chloroplast genomic landscape and annotation towards comparative chloroplast genomes of Rhamnaceae - Kwanjeera Wanichthanarak; Intawat Nookaew; Phongthana Pasookhush; Thidathip Wongsurawat; Piroon Jenjaroenpun; Namkhang Leeratsuwan; Songsak Wattanachaisaereekul; Wonnop Visessanguan; Yongyut Sirivatanauksorn; Narong Nuntasaen; Chutima Kuhakarn; Vichai Reutrakul; et al. (My University, 2023)
Additional file 6: Table S8. The Ka/Ks ratio values and nucleotide diversity of protein-coding genes of the Rhamnaceae
Keywords: Rhamnaceae; Genomics and Phylogenetic Studies